Study on Adolescents Reproductive Health & Problems in a Tertiary Care Hospital, Chattogram - Tahmina Sultana, Begum; Noor, Serajun; Begum, Tahera; Sabina Yeasmin, Most; Akhter, Salma; Mabud, Farahnaz (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Adolescence is a stage where the physical and psychological development of a child takes place. Inother words, teenagers passing the years between the puberty and adulthood, from ages 10-19 years. Adolescents are likely to face a range of health and social challenges, for instance initiation of sexual activity while there is still lack of adequate knowledge and skill. High prevalence of early marriage and child bearing are associated with higher rate of morbidity and mortality. They are also in higher risk of unwanted pregnancy, unsafe abortion and sexually transmitted infections. The main objective of this study is to suggest the strategies for improvement of adolescents reproductive health status in Bangladesh. Materials and methods: This retrospective observational study was conducted in the Obs and Gynae Department of Chattagram Maa-O-Shushu Hospital Medical College (CMOSHMC) from July to December 2022. Total 436 adolescents were included in this study who were admitted in Obs and Gynae Department instudy period. All cases reviewed retrospectively from in patients records. An inclusion criterion of age in this study is 10-19 years. Results: A Total 436 patients were enrolled in this study with age limit between 10- 19 years. Total Obstetric patients were 360 (82.57 %). Among them antenatal patients were 348 (97 %), postnatal patients were 12 (3%). Among antenatal patients primipara 344 (99 %), multi para (2nd pregnancy) 4 (1%). Total delivery occurred in 302 patients. Vaginal delivery occurred in 147 patients (49 %), cesarean section were needed in 140 patients (46%). Repair of perineal tear done in 2 post natal patients. Secondary wound closure was done in 1 patient. Conservative management was given to 70 patients. Sexual abuse in 3 patients, came with 14, 16 and 25 weeks of pregnancy and medical termination were done in all cases. Maternal death was 1 (4.2%) due to primary PPH following LSCS due to central placenta Previa with postoperative cardiac arrest. Total baby delivered 302, alive 287(95%), intrauterine death 15 (5%). LBW (Low Birth Weight) 49 (17 % of alive baby ), IUGR (Intrauterine Growth Restriction) 6 (2%), NND (Neonatal Death) 5 (1.7%). Total Gynae patients admitted were 76 (17.43%), abortion related complications were 52 (68%), menstrual abnormality were 7(9.2%), ruptured ectopic pregnancy following sexual abuse was 1 (0.92% of total patients ) . Conclusion: There is growing attention being paid to improving access to quality maternal care for pregnant and parenting adolescents preventing pregnancy among adolescents are fundamental to achieving positive health outcomes across the life course and imperative for achieving the SDGS (Sustainable Developmental Goals) related to maternal and newborn health. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 60-63